Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Backward and forward simulation of polycyclic aromatic hydrocarbons by the grid-scale model _validation and applications for environmental management - Ming-Tsuen Hsieh; Wen-Yu Chung; Shoiw-Mei Tseng; Pei-Chi Shih; Shau-Ku Huang; Chon-Lin Lee (Atmospheric Environment, 2024)

Photoelectrochemical degradation of TMAH by green synthesized silver modified titanate nanotube arrays - Wu-Xing Chen; Ku-Fan Chen; Ken-Ling Chang; Wei-Hsiang Chen; Chia-Hua Lin; Chia-Hung Chen; Ci-Yi Shih; Yi-Chun Chen; Yen-Ping Peng (Journal of Environmental Chemical Engineering, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

Chronic ketamine abuse is associated with orexin-A reduction and ACTH elevation - Ming-Chyi Huang; Chun-Hsin Chen; Lian-Yu Chen; Hu-Ming Chang; Chih-Ken Chen; Shih-Ku Lin; Ke Xu (Psychopharmacology, 2020)

Cognitive profile of ketamine-dependent patients compared with methamphetamine-dependent patients and healthy controls - Liang-Jen Wang; Chih-Ken Chen; Shih-Ku Lin; Yi-Chih Chen; Ke Xu; Ming-Chyi Huang (Psychopharmacology, 2018)

Fractional Thermolysis by Bipolar Radiofrequency Facilitates Cutaneous Delivery of Peptide and siRNA with Minor Loss of Barrier Function - Woan-Ruoh Lee; Shing-Chuan Shen; Chi-Kuang Sun; Ibrahim A. Aljuffali; Shih-Yun Suen; Yin-Ku Lin; Jhi-Joung Wang; Jia-You Fang (Pharmaceutical Research, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Association analysis of SOD2 variants with methamphetamine psychosis in Japanese and Taiwanese populations - Kazuhiko Nakamura; Chih-Ken Chen; Yoshimoto Sekine; Yasuhide Iwata; A. Anitha; El-Wui Loh; Nori Takei; Atsuko Suzuki; Masayoshi Kawai; Kiyokazu Takebayashi; Katsuaki Suzuki; Yoshio Minabe; et al. (Human Genetics, 2006)